(untitled) (Dinamika Ilmu, 2022)
This study aimed to examine whether spirituality, religiosity, and competence can predict teacher performance. To prove this, a study was conducted on 90 Madrasah teachers in Samarinda as the sample in this study. The research sample was selected randomly, the number of which was determined based on the Slovin formula with a precision level of 0.10 (N=867). To obtain empirical data, researchers used a questionnaire on spirituality, religiosity, competence, and teacher performance. The research data were analyzed using Multiple Linear Regression with the SPSS V26 program. The analysis results showed a significant level of p <0.05 with a relationship strength of 0.843, which means that there is a significant relationship between spirituality, religiosity, and competence with teacher performance. Simultaneously, the contribution of the three independent variables to teacher performance was 53.8%, while partially, each independent variable contributed 50.8% (spirituality), 24% (religiosity), and 59.8% (competence). The implication is that these findings prove that one cannot rely solely on competency factors to get good performance from teachers. Although competence has the highest contribution, it also takes a religiosity factor that will give direction to individuals in their work, namely worshipping Allah SWT, and spiritual factors that provide meaning and prosperity in life. Thus, it can be concluded that the level of teacher performance can be predicted through the teacher’s spirituality, religiosity, and competence.